Analyzing the genetic profile of autistic children and adolescents with minimal verbal abilities - Guerrera, Silvia; Venezia, Ilaria; Logrieco, Maria Grazia; Casula, Laura; Capolino, Rossella; Digilio, Maria Cristina; Dentici, Maria Lisa; Macchiaiolo, Marina; Casciani, Federico; Cortellessa, Fabiana; Sinibaldi, Lorenzo; Bartuli, Andrea; et al. (Frontiers in Genetics, 2026)
IntroductionComprehensive care for autistic youth with severe symptoms and language impairment includes genetic testing to find underlying causes. Identifying a genetic diagnosis helps determine prognosis, guide treatment, assess recurrence risk, and connect families with targeted resources and support networks.MethodsThis cross-sectional study analyzed retrospectively data of a cohort of 60 Autism Spectrum Disorder Minimally Verbal (MV) past age 5 children and adolescents who underwent several genetic investigations and were included in an evaluation protocol including cognitive, adaptive, psychiatric, parental stress and autism characteristics’ evaluations to identify whether there were any specific clinical or genetic characteristics in the group of minimally verbal autistic individuals.ResultsThe percentage of genetic disorders detected in the series is 22.6%. Two groups of MV autistic individuals were defined: those without a known genetic cause (n = 46, neuropsychological data available for 32 individuals) and those with an associated genetic condition (n = 14, neuropsychological data available for 8 individuals). Most participants in both groups scored below 70 on Nonverbal Intelligence Quotient (NVIQ) (77.5% in the first group versus 77.7% in the latter) and adaptive functioning was impaired in both groups, without significant differences. Autism severity, measured by the ADOS-2, was significantly higher in individuals without causative alteration, particularly in Total Comparison Score. However, no differences were found between groups in restricted and repetitive behaviors. CBCL showed high levels of internalizing and externalizing problems in both groups, with no differences. Similarly, parental stress levels were high in both groups.DiscussionThis is the first study analyzing the genotype-phenotype correlation in MV autistic individuals. In this sample, the prevalence of genetic syndromes was found to be twice as high as in the general autistic population (22.6% versus 10%). Regarding the autistic characteristics’ severity which appear to be higher in individuals without genetic causative alteration and the absence of significant differences in cognitive, functional and behavioural characteristics, we hypothesised that, in the MV autistic population without genetic causative alteration, there are specific and unknown characteristics of the MV profile which have a greater impact than the individual genetic condition reported.